2016
DOI: 10.1002/mnfr.201500991
|View full text |Cite
|
Sign up to set email alerts
|

Gene specific epigenetic regulation of hepatic folate transport system is responsible for perturbed cellular folate status during aging and exogenous modulation

Abstract: Promoter hypermethylation of RFC and promoter hypomethylation of ABCG2 may be attributed to the down regulation of RFC and up regulation of ABCG2 at mRNA and protein levels in conditions of 3 and 5 months of folate deficiency in the adult group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Low levels of dietary folate cause aberrant DNA methylation pattern and can lead to perturbed biosynthesis [10, 41]. Therefore, we determined the methylation profile of the Esr1 , Cav1 , and Elavl1 promoter regions in the human sperm DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of dietary folate cause aberrant DNA methylation pattern and can lead to perturbed biosynthesis [10, 41]. Therefore, we determined the methylation profile of the Esr1 , Cav1 , and Elavl1 promoter regions in the human sperm DNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific mechanism was still unclear. Specially, lack of folic acid led to demethylation of ABCG2 (Ahmad Najar et al, 2016), lack of Vitamin D led to hypermethylation of CYP24A1 and CYP27B1 (Anderson et al, 2015; Wang et al, 2020). The folic acid excretion cells increased or decreased when folic acid was excessive or deficient.…”
Section: Resultsmentioning
confidence: 99%
“…This process was transported by ABCG2 and the expression of ABCG2 was regulated by methylation. Finally, the total folic acid maintained stable (Ahmad Najar et al, 2016). 24-Hydroxylase encoded by the CYP24A1 gene was a catabolic enzyme and both 25(OH)D and 125(OH)2D were catabolized by the 24-hydroxylase into inactive metabolites, thereby lowering the vitamin D levels (Wang et al, 2020).…”
Section: Obesity and Dietmentioning
confidence: 99%
“…Additionally, women belonging to lower educational level and SES often have infrequent antenatal visits, which diminishes their opportunities for dietary assessments, necessary adjustments, and adequate supplementation ( 32 , 33 ). While some studies suggest that older women are more likely to adhere to healthier diets ( 32 ), animal research indicated that folate-modulated DNA methylation decreased with age ( 34 , 35 ). This could explain the notably lower serum methionine levels observed in pregnant women aged 35 and above in this study.…”
Section: Discussionmentioning
confidence: 99%